2015
DOI: 10.1007/s00394-015-0896-z
|View full text |Cite|
|
Sign up to set email alerts
|

Habitual dietary intake of β-carotene, vitamin C, folate, or vitamin E may interact with single nucleotide polymorphisms on brachial–ankle pulse wave velocity in healthy adults

Abstract: Higher intake of dietary vitamin C, folate, and vitamin E may be related to high baPWV in healthy Korean men who are minor allele homozygotes of rs4961. In healthy Korean women, dietary folate, β-carotene, and vitamin E intake may affect baPWV differently according to rs4961, rs10817542, rs719856, or rs5443 genotype. Greater dietary intake of these nutrients may protect those that are genetically vulnerable to stiffening of the arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…In our study, the multivariate CCA analysis showed baPWV to have a negative association in both women and men with the carotenoids, retinol and vitamins considered in the study. These results are in accordance with the work done by Park et al [27] in a cohort of multicultural communities in Korea, where the intake of β-carotene, vitamin C, folate, or vitamin E was also found to be negatively associated with baPWV.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the multivariate CCA analysis showed baPWV to have a negative association in both women and men with the carotenoids, retinol and vitamins considered in the study. These results are in accordance with the work done by Park et al [27] in a cohort of multicultural communities in Korea, where the intake of β-carotene, vitamin C, folate, or vitamin E was also found to be negatively associated with baPWV.…”
Section: Discussionsupporting
confidence: 93%
“…Association studies have demonstrated that ZNF618 may be involved in the occurrence of cleft lip [33], high blood pressure [34], kidney diseases [35] and, in women, in brachial-ankle pulse wave velocity and arterial stiffness [36, 37]. On the basis of these clinical characteristics, we excluded this gene as a candidate gene.…”
Section: Discussionmentioning
confidence: 99%
“…Combined supplementation of vitamins C and E was ineffective in improving endothelial function in 14 randomized trials, including 597 participants, regardless of age, duration, dose, or baseline plasma concentration of vitamins [ 99 ]. Park et al demonstrated that higher intake of beta-carotene, vitamins C, E, and folate may protect individuals genetically vulnerable to stiffening of the arteries, in a study including 3,198 healthy men and women from the Korea Multirural communities, quantifiyng dietary intakes by a food frequency questionnaire [ 111 ].…”
Section: Vitamin Ementioning
confidence: 99%